PERTANGGUNGJAWABAN PIDANA DALAM KEJAHATAN SIBER (CYBERCRIME) DI ERA DIGITAL: KAJIAN PUSTAKA TERHADAP KETERBATASAN REGULASI HUKUM PIDANA INDONESIA - Gunawan Widjaja (INTELIGENSIA MEDIA, 2026)
The development of information and communication technology in the digital age has brought significant changes to various aspects of human life, including the emergence of a new form of technology-based crime: cybercrime. This study aims to analyze criminal liability in cybercrime and identify the limitations of Indonesian criminal law regulations in addressing cybercrime. The study employs a normative legal research method using a literature review approach. The findings indicate that although Indonesia has established a legal foundation for criminal liability through the Criminal Code (KUHP) and the Law on Information and Electronic Transactions (UU ITE), the effectiveness of law enforcement remains hindered by scattered regulatory limitations, the continued existence of legal gaps regarding certain forms of cybercrime, inconsistencies between the Criminal Code and the Electronic Information and Transactions Law, weaknesses in the regulation of electronic evidence, as well as limitations in human resources and digital forensic infrastructure. This study concludes that strengthening criminal liability for cybercrime requires a more comprehensive reform of criminal law, regulatory harmonization, enhanced technical capacity of law enforcement agencies, and strengthened international cooperation to address the transnational nature of cybercrime.